Aprendizaje mediante uso de infografías didácticas como recurso educativo de la Biología - Chicaiza Padilla, José Pablo (2023)
Abstract The research titled “Learning through the use of didactic infographics as an educational resource of Biology” had the objective of determining the perception of didactic infographics as an educational resource for the first year of Baccalaureate students of the “Atahualpa Fiscal Educational Unit” to improve the learning of Biology. The study was framed within the quantitative approach; the research design was the non-experimental study; for data collection, the survey technique was applied using the questionnaire instrument of 10 questions with multiple choice answers. The population considered for this research was 87 first-year high school students; the sample was non-probabilistic and intentional since the population involved was not extensive, so we proceeded to work with the entire universe. The characterization, elaboration, and application of infographics with interesting, eye-catching, and more didactic content sparked interest in learning. This Biology educational resource was applied from the beginning of the second partial of the first semester until the end of the academic period. Keywords: Didactic infographics and education, Biology learning. Reviewed by: Lic. Jenny Freire Rivera ENGLISH PROFESSOR C.C. 0604235036